RNA aptamers that recognize amyloid β oligomers in AppNL‐G‐F/NL‐G‐F mice as a model of arctic Alzheimer disease: Developing topics. (7th December 2020) - Murakami, Kazuma; Obata, Yayoi; Kawase, Taiji; Hirose, Kenji; Izuo, Naotaka; Shimizu, Takahiko; Irie, Kazuhiro
Abstract: Background: RNA aptamers have garnered attention for diagnostic applications due to their ability to recognize diverse targets. Oligomers of Aβ42 are among the most difficult molecules for aptamer recognition because they are prone to aggregate in heterogenous forms. In addition to designing haptens for in vitro selection of aptamers, the difficulties involved in determining their effect on Aβ42 oligomerization impede aptamer research. We previously developed three RNA aptamers (E22P‐AbD4, ‐AbD31, and ‐AbD43) with high affinity for protofibrils (PFs) derived from a toxic Aβ42 dimer (Murakami, K. et al., J. Biol. Chem . 2020, 295, 4870–4880). In this study, these aptamers were further validated for specificity to oligomers using ion‐mobility mass spectrometry and a knock‐in App NL‐G‐F/NL‐G‐F mouse harboring the Arctic mutation (E22G‐Aβ). Method: The ability to inhibit oligomer formation of Aβ42 was evaluated by ion mobility‐mass spectrometry, which can avoid the disruption of non‐covalent interactions among Aβ oligomers without using organic solvents, leading to observation of the near‐native status of oligomers in the presence of aggregation inhibitors. The immunostaining of Aβ oligomers in the brain was carried out using a knock‐in App NL‐G‐F/NL‐G‐F mouse that is prone to induce PF formation as a Arctic AD model, provided by Dr. Saido (RIKEN). The prediction of G‐quadruplex was estimated based on quadruplex‐forming G‐rich sequences (QGRS) Mapper. Result: RNA aptamers recognized diffuse aggregates, which likely originated from PFs in a knock‐in App NL‐G‐F/NL‐G‐F mouse in addition to a PS2Tg2576 mouse. E22P‐AbD43 formed the adducts with Aβ42 monomer and dimer, leading to suppression of further oligomerization. In particular, the G‐quadruplex structure might be relevant to the binding of the aptamers (E22P‐AbD4 and ‐AbD31) to oligomers. Conclusion: The current data support the utility of these RNA aptamers as a promising diagnostic tool for AD research.